Performance Allowances in Relation to Work Unit Performance Load - Abdullah, Sudirman; Pelu, Hanafi (JENTRE, 2024)
Allowances are computed based on individual performance successes, such as workload, task difficulty, and contribution to corporate goals. The purpose of this article is to describe how performance allowance is paid depending on performance burden in the work unit (case study at the Ministry of Religious Affairs). The research method is qualitative, and the research type is descriptive. The findings revealed that paying performance-based performance allowances in Ministry of Religion work units is a strategic step toward encouraging better employee performance. However, its execution is fraught with difficulties, such as a lack of clarity in defining performance measures and uneven workload distribution. Allowance inequity can lower employee morale and negatively impact organizational productivity. As a result, inequity necessitates periodic reviews and revisions to make the allowance system more equal and efficient.